Development of pipe crawling robots with vibratory drives and investigation of their kinematic parameters - V. Mištinas; B. Spruogis (Transport, 2002)
In the article the classification of pipe crawling robots with vibratory drives is presented, their advantages and imperfections are reviewed. The schemes of the construction of a pipe crawling robot with a vibratory impulse drive and a pipe crawling robot with a vibratory pneumatic drive are discussed. The dynamic models of a robot with a vibratory impulse drive and of a robot with a vibratory pneumatic drive were developed and the equations of their movement were formed and written.